2016
DOI: 10.1021/acsami.6b09204
|View full text |Cite
|
Sign up to set email alerts
|

Micelles with Sheddable Dendritic Polyglycerol Sulfate Shells Show Extraordinary Tumor Targetability and Chemotherapy in Vivo

Abstract: Cancer nanomedicines are typically stealthed by a poly(ethylene glycol) layer that is important to obtain extended blood circulation and elevated tumor accumulation. PEG stealth, however, also leads to poor tumor cell selectivity and uptake thereby reducing treatment efficacy. Here, we report that biodegradable micelles with sheddable dendritic polyglycerol sulfate (dPGS) shells show an unusual tumor targetability and chemotherapy in vivo. The self-assembly of dPGS-SS-poly(ε-caprolactone) amphiphilic block cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 61 publications
0
37
0
11
Order By: Relevance
“…Interestingly, the cores of the PTX-loaded NPs have some influence on particle size, as compared to the blank NPs, PTX-loaded NPs particle sizes are smaller indicating that after the introduction of the drug, the hydrophobic interaction forces between it and the carrier are enhanced resulting in decreased particle sizes. The sizes of all the NPs are below 300 nm and have a narrow size distribution (PDI <0.45), which is appropriate for tumor targeting by the EPR effect, and they have a size distribution that is suitable for intravenous administration (Song et al., 2016 ; Zhong et al., 2016 ; Wang et al., 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the cores of the PTX-loaded NPs have some influence on particle size, as compared to the blank NPs, PTX-loaded NPs particle sizes are smaller indicating that after the introduction of the drug, the hydrophobic interaction forces between it and the carrier are enhanced resulting in decreased particle sizes. The sizes of all the NPs are below 300 nm and have a narrow size distribution (PDI <0.45), which is appropriate for tumor targeting by the EPR effect, and they have a size distribution that is suitable for intravenous administration (Song et al., 2016 ; Zhong et al., 2016 ; Wang et al., 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among various PTX delivery systems, nano-scale biopolymers hold numerous advantages (Bhirde et al., 2010 ; Madane & Mahajan, 2016 ; Zhong et al., 2016 ; Huang et al., 2017 ), including their ability to improve drug stability and pharmacological properties, offer enhanced longevity in the blood and they provide an eligible carrier system that can protect and effectively deliver drugs to the target site by integrating different treatment strategies into one platform in order to minimize side effects. Specifically, compared with conventional medicines, nanoparticle drug delivery systems are able to exhibit passive/active target properties and controlled or sustained drug-release kinetics (Xie et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is a biocompatible and highly degradable hydrogel that could be used for biomedical applications. The same group further reported the synthesis of a dPGS-SS-PCL amphiphilic block copolymer, with an M n of 4.8−3.7 kg/mol and a negatively charged sulfonate surface, capable of self-assembling into small sized micelles (Figure 15) [229]. dPGS-SS-PCL block polymer was obtained via a copper-free strain-promoted azide−alkyne cycloaddition between linear PCL-SS-cyclooctyne (M n = 3.7 kg mol −1 ) and dendritic azide-dPGS (M n = 4.8 kg/mol, sulfation 88%).…”
Section: Functionalized Polyglycerol/poly(ε-caprolactone) Copolymersmentioning
confidence: 99%
“…For example, Neibert et al showed the facile expansion of the dendrimer core from G0 to hydroxyl-terminated G1 dendrimer through the copper(I)-catalyzed alkyne-azide cycloaddition (CuAAC) click reaction [ 81 ]. The internal core structure in high-generation hyperbranched structures, in principle, can enable dendrimers to adapt and encapsulate therapeutic agents [ 83 , 84 ]. However, the major applications of dendrimers have been through tailoring their backbone and surfaces.…”
Section: Dendrimersmentioning
confidence: 99%